MANAGEMENT OF DA'WAH TRAINING IN IMPROVING THE QUALITY OF STUDENTS' DA'WAH AT THE DARUL ARAFAH RAYA ISLAMIC BOARDING SCHOOL - Ginting, Jihad Al-Qadri; Soiman, Soiman (Journal Analytica Islamica, 2025)
The development of communication technology has expanded the reach of da'wah, but also presents challenges in maintaining the quality and direction of da'wah messages so that they remain in accordance with Islamic values. This study aims to analyze the management of da'wah training at the Darul Arafah Raya Islamic Boarding School, focusing on four management functions: planning, organizing, implementing, and monitoring and evaluation. The research method uses a qualitative descriptive approach with a case study design, through in-depth interviews, participatory observation, and documentation analysis. The results show that muhadharah-based da'wah training at the Islamic boarding school has been implemented systematically and effectively, supported by the role of musyrif as mentors, an adaptive curriculum, and a visual narrative strategy in strengthening the communication skills of students. In conclusion, the management of da'wah training at this Islamic boarding school is able to produce da'i cadres who are competent, moderate, and ready to da'wah in modern society.